PENERAPAN PRINSIP MANAJEMEN KELAS DALAM MENGATASI PROBLEMATIKA KERAGAMAN BELAJAR - Dewi, Risna; Irwansya, Muh.; Mardiansyah, Mardiansyah; Syahril, Syahril (DIDAKTIKA, 2022)
The role of classroom management is needed in overcoming students' learning problems. The ability of teachers to manage the classroom is very important because the implementation of classroom management can affect student learning progress. The type of research used is descriptive qualitative with data collection methods, namely interviews, observations and documentation. The application of classroom management principles in the teaching and learning process includes being warm and enthusiastic, providing challenges, being flexible, emphasizing on the positive and instilling a disciplined attitude. The problems faced by students in learning are lack of concentration, motivation, understanding of lessons and lack of mental ability, lack of facilities at school. The contribution of class management in overcoming the problems of student learning diversity is that teachers and students cooperate with each other in managing the class, class management has a role in achieving the success of teachers in overcoming the problems that occur.